Role of angiotensin II and vasopressin receptors within the supraoptic nucleus in water and sodium intake induced by the injection of angiotensin II into the medial septal area - Antunes, V.R. [UNESP]; Camargo, G.M.P.A. [UNESP]; Saad, R. [UNESP]; Saad, W.A. [UNESP]; Luiz, A.C. [UNESP]; Camargo, L.A.A. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1998)
In this study we investigated the effects of the injection into the supraoptic nucleus (SON) of non-peptide AT1- and AT2-angiotensin II (ANG II) receptor antagonists, DuP753 and PD123319, as well as of the arginine-vasopressin (AVP) receptor antagonist d(CH2)5-Tyr(Me)-AVP, on water and 3% NaCl intake induced by the injection of ANG II into the medial septal area (MSA). The effects on water or 3% NaCl intake were assessed in 30-h water-deprived or in 20-h water-deprived furosemide-treated adult male rats, respectively. The drugs were injected in 0.5 µl over 30-60 s. Controls were injected with a similar volume of 0.15 M NaCl. Antagonists were injected at doses of 20, 80 and 180 nmol. Water and sodium intake was measured over a 2-h period. Previous administration of the AT1 receptor antagonist DuP753 into the SON decreased water (65%, N = 10, P<0.01) and sodium intake (81%, N = 8, P<0.01) induced by the injection of ANG II (10 nmol) into the MSA. Neither of these responses was significantly changed by injection of the AT2-receptor antagonist PD123319 into the SON. on the other hand, while there was a decrease in water intake (45%, N = 9, P<0.01), ANG II-induced sodium intake was significantly increased (70%, N = 8, P<0.01) following injection of the V1-type vasopressin antagonist d(CH2)5-Tyr(Me)-AVP into the SON. These results suggest that both AT1 and V1 receptors within the SON may be involved in water and sodium intake induced by the activation of ANG II receptors within the MSA. Furthermore, they do not support the involvement of MSA AT2 receptors in the mediation of these responses.
Keywords: angiotensin II; AT1 receptors; AT2 receptors; V1 receptors; water intake; sodium intake; medial septal area; supraoptic nucleus; rats